2020
DOI: 10.1097/qco.0000000000000618
|View full text |Cite
|
Sign up to set email alerts
|

Updates in trichomonas treatment including persistent infection and 5-nitroimidazole hypersensitivity

Abstract: Purpose of the review: The purpose of this review is to update information on treatment of T. vaginalis. Trichomonas vaginalis is estimated to be the most common treatable sexually transmitted infection (STI) In the world and is associated with poor birth outcomes, cervical cancer, sperm motility and morphology issues, and HIV acquisition and transmission. Recent findings:The efficacy of the recommended 2 gram oral single-dose metronidazole (MTZ) for the treatment of T. vaginalis in women has recently been cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 41 publications
0
10
0
2
Order By: Relevance
“…5,6,7 Trichomonas vaginalis infection prevalence in pregnant women ranges from 17% to 20% in Africa, 16% to 53% in the United States and 0.8% in Asia. 8 Studies that have been conducted in South African pregnant women have reported prevalence rates of 15.3% 5 and 20.2%. 7 Several risk factors associated with T. vaginalis infection have been reported including older age, co-infection with other STIs, 9,10 sexual behaviour, socioeconomic status and phase of menstrual cycle.…”
Section: Introductionmentioning
confidence: 99%
“…5,6,7 Trichomonas vaginalis infection prevalence in pregnant women ranges from 17% to 20% in Africa, 16% to 53% in the United States and 0.8% in Asia. 8 Studies that have been conducted in South African pregnant women have reported prevalence rates of 15.3% 5 and 20.2%. 7 Several risk factors associated with T. vaginalis infection have been reported including older age, co-infection with other STIs, 9,10 sexual behaviour, socioeconomic status and phase of menstrual cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Paromomycin is an aminoglycoside with a different mechanism of action (destruction of ribosomal RNA) than 5-nitroimidazoles (inhibition of nucleic acid synthesis by DNA disruption and/or inhibition of enzymes involved in antioxidant defense) (Leitsch et al ., 2009; Van Gerwen and Muzny, 2019); combination use of these medications may provide a synergistic effect. It is important to note that all intra-vaginal formulations need to be made at a compounding pharmacy and may be costly (Muzny et al ., 2020). In addition, intra-vaginal paromomycin can cause vaginal ulceration and should be discontinued if this occurs, at which time ulcerations may spontaneously regress (Van Gerwen and Muzny, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Trichomonas vaginalis es el protozoario parásito identificado como agente etiológico de la tricomoniasis, responsable de hasta el 30% de las infecciones de transmisión sexual no virales en el mundo 1 . La tricomoniasis se relaciona con cáncer cervical, enfermedades inflamatorias pélvicas atípicas, infertilidad, ruptura prematura de la membrana placentaria y el incremento de transmisión del VIH 2. Su prevalencia mundial en mujeres de 15-49 años es 5.3% y de 0.6% en hombres 3 , sin embargo algunos autores reportan que las frecuencias más altas se encuentran en mujeres de 46 a 55 años de edad 2,4 . En México se reportan prevalencias entre 15-20% 5 .…”
Section: Introductionunclassified
“…En México se reportan prevalencias entre 15-20% 5 . Esta infección es frecuentemente asintomática (85% en mujeres), lo que facilita su transmisión 1,3 ; cuando los síntomas de la infección se presentan, incluyen leucorrea abundante, amarillo verdosa, fétida y espumosa, frecuentemente en mujeres es referida disuria, prurito y dispareunia, a la exploración se observa el llamado "cérvix de fresa" por las hemorragias puntiformes y dilatación de capilares 1 . Los métodos tradicionales para su identificación incluyen microscopía y cultivo, recientemente se han desarrollado métodos moleculares mucho más sensibles 2 .…”
Section: Introductionunclassified